Determination of Indicators in the Information System Development for Monitoring and Evaluating Nutritional Interventions for Stunting Children - Pipit Wiliyanarti; Yuanita Wulandari; Dede Nasrullah (Health and Technology Journal (HTechJ), 2023)
Stunting is a serious problem that requires sustainable management and commitment from the state and all levels of society. Stunting data needs to be collected properly to develop strategies to eliminate the incidence of stunting. the information system for monitoring and evaluating nutritional interventions for stunting children is an information system that can be used for accelerated programs to eliminate the incidence of stunting. This study's aim was to analyze factors related to the use of the information system for monitoring and evaluating nutritional interventions for stunting children. A cross-sectional correlational design was used in this study. The variables were knowledge, data management, infrastructure, and the information system for monitoring and evaluating nutritional interventions for stunting children. One hundred and five stunting cadres were selected using a random sampling technique. Data collection was performed using self-report questionnaires. The Logistic Regression test was used to analyze the data. This study found that data management (p-value: 0.009), knowledge (p-value (0.000), and infrastructure (p-value: 0.018) elements affect the utilization of the information system for monitoring and evaluating stunting child nutrition interventions.  In sum, the continuity of the information system for monitoring and evaluating stunting child nutrition interventions is expected to eliminate the incidence of stunting. Information systems for monitoring and evaluating stunting child nutrition interventions can be used as evidence to recommend strategies to eliminate stunting incidence. Therefore, community participation and government commitment are needed.